2017
DOI: 10.1080/09585192.2017.1314313
|View full text |Cite
|
Sign up to set email alerts
|

HRM, climate and employee well-being: comparing an optimistic and critical perspective

Abstract: A growing number of studies investigating the linkage between HRM and employee well-being largely supports a positive perspective on HRM (HRM positively affects employee well-being). There is only a limited body of empirical evidence that supports a critical perspective (HRM negatively affects well-being), or combines both perspectives. The present paper contributes to an understanding of the relationship between HRM and well-being, by testing both perspectives simultaneously. Following a positive perspective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 56 publications
6
71
0
2
Order By: Relevance
“…As Leroy et al () observed, the multifaceted nature of managing people in organisations calls for integration of human resource and leadership practices that promote workplace mutuality and ultimately, sustainable management of human resources. In this task, future research should abandon the continued focus on comparing the conflict and mutual gains perspective in HPWS research (Ogbonnaya & Messersmith, ; Veld & Alfes, ). Instead, grounded in SDT, this research should draw on conceptual work that proposed well‐being‐oriented HPWS (Guest, ) and leadership (Jiménez et al, ) or servant leadership to examine how the latter is shaped by the former and the processes through which they influence well‐being (variously operationalised) and ultimately, employee performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Leroy et al () observed, the multifaceted nature of managing people in organisations calls for integration of human resource and leadership practices that promote workplace mutuality and ultimately, sustainable management of human resources. In this task, future research should abandon the continued focus on comparing the conflict and mutual gains perspective in HPWS research (Ogbonnaya & Messersmith, ; Veld & Alfes, ). Instead, grounded in SDT, this research should draw on conceptual work that proposed well‐being‐oriented HPWS (Guest, ) and leadership (Jiménez et al, ) or servant leadership to examine how the latter is shaped by the former and the processes through which they influence well‐being (variously operationalised) and ultimately, employee performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this task, future research should abandon the continued focus on comparing the conflict and mutual gains perspective in HPWS research (Ogbonnaya & Messersmith, 2018;Veld & Alfes, 2017). Instead, grounded in SDT, this research should draw on conceptual work that proposed well-being-oriented HPWS (Guest, 2017) and leadership (Jiménez et al, 2017) or servant leadership to examine how the latter is shaped by the former and the processes through which they influence well-being (variously operationalised) and ultimately, employee performance.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Existing literature has considered employees' perception of organizational climate as a key mediating mechanism linking HRM to organizational outcomes (e.g., Bowen & Ostroff, 2004;Veld & Alfes, 2017). Veld and Alfes (2017) demonstrated how HRM will enhance employee wellbeing via a climate for wellbeing, and will negatively affect employee wellbeing via a climate for efficiency.…”
Section: The Mediating Role Of An Involvement Climatementioning
confidence: 99%
“…Building on Grant et al . 's () model, HRM research typically considers one or more of three types of well‐being: happiness (e.g., job satisfaction, commitment), health (e.g., stress, exhaustion) and social (e.g., trust, social support) well‐being (e.g., Baluch, ; Heffernan and Dundon, ; Veld and Alfes, ). In their review, Van de Voorde et al .…”
Section: Introductionmentioning
confidence: 99%
“…Their review showed a strong need for more balanced studies incorporating multiple dimensions of well‐being, especially those in a clear trade‐off (Van de Voorde et al ., ; Wood et al ., ). A few follow‐up studies have taken such a balanced approach (Boxall and Macky, ; Heffernan and Dundon, ; Veld and Alfes, ), yet show inconsistent findings. This additionally suggests a need to discover boundary conditions explaining under which circumstances organizations can avoid this inherent trade‐off, ensuring that employee well‐being (in all of its facets) as well as performance is fostered (Peccei et al ., ).…”
Section: Introductionmentioning
confidence: 99%